Effectiveness Of Professional Teacher Education In Developing Educational Technology Skills In The Digital Era - Erni Ratna Dewi; Mulyadi (PT. Anagata Sembagi Education, 2024)
This research discusses the effectiveness of professional teacher education in developing educational technology skills in the digital era, focusing on mastery of technological competencies, management of online learning, and creativity in teaching. In an increasingly digitized context, teacher education programs must be able to answer the challenges faced in utilizing technology in the learning process. This research uses a qualitative approach with a case study design, involving 10-15 teachers who have attended professional education programs related to educational technology. Data were collected through in-depth interviews, participant observation and documentation analysis to gain comprehensive insights. The results show that professional teacher education significantly improves technology skills, helping teachers to be more confident in using digital tools and creating interactive learning experiences. However, implementation challenges, such as limited internet access and inadequate devices, are barriers that need to be overcome through institutional support. This study provides recommendations for the improvement of professional teacher education programs to be more effective in preparing teachers for the evolving demands of education in the digital era.